Arabic Language Learning For Elementary Schools During Pandemic Covid-19 - Muhammad Yusuf Salam; Imam Asrori; Adam Mudinillah; Muhammad Abdul Ali Sayyid Ibrahim (Ijaz Arabi Journal of Arabic Learning, 2022)
In the COVID-19 outbreak, the implementation of learning which is usually carried out face-to-face has been shifted to virtual form. The performance of education during the pandemic has undergone significant changes so that the problems found in its implementation can be studied to find solutions to these problems. This study was conducted to obtain data on the performance and progress of Arabic language learning in Islamic boarding schools during the COVID-19 pandemic in Indonesia. The method used in this research is descriptive qualitative through library research. The study was conducted to provide a clear, objective, systematic, analytical, and critical description of the implementation of Arabic language learning at Madrasah Ibtidaiyah Tanah Datar during the COVID-19 pandemic. This research was conducted in 2021 in one of the Ibtidaiyah Madrasah in Tanah Datar Regency. The research results are sourced from several instruments that have been prepared previously, such as questionnaires or research questionnaires to serve as a supporting tool in conducting direct observations and interviews with the research object. In addition, the data of this study were sourced from the results of interviews with the Ibtidaiyah madrasah. His study results indicate that learning Arabic during the pandemic has advantages and disadvantages. The obstacles found in the implementation of learning can be in the form of the psychological conditions of students affected by the COVID-19 pandemic, less than optimal teacher performance in preparing lessons, internal family problems, and the environmental conditions of the surrounding community.